Selective Detection of Copper Ions and Biological Activities of Isoniazid Schiff Bases. Issue 12 (21st March 2023) - Hemalatha, G. Muni; Thirunavukkarasu, Kandasamy; Kumar, C. Ramesh; Thamim, Masthan; Thirumoorthy, Krishnan
Abstract: Following mechanical milling, the condensation reaction of the corresponding heterocyclic aldehydes with Isoniazid yields the Schiff base (E)‐N′‐((1H‐pyrrol‐2‐yl) methylene)isonicotinohydrazide (S1) and (E)‐N′‐(Thiophen‐2‐ylmethylene)isonicotinohydrazide (S2) supported heterocyclic derivatives. The structures of the Schiff bases, S1 and S2 were confirmed by 1 H NMR, 13 C NMR and IR spectroscopy. Copper ions (Cu 2+ ) were trapped by S1 in DMSO to form the yellow‐coloured complex Cu‐(E)‐N′‐((1H‐pyrrol‐2‐yl)methylene) isonicotinohydrazide (Cu 2+ +S1) with high sensitivity and selectivity. But the same ligand S1 could not be able to capture other metal ions tested for this work (namely, Co 2+, Ni 2+, Zn 2+, Mn 2+, Hg 2+, Cd 2+, Pb 2+, Fe 2+, and Fe 3+ ) in DMSO. UV‐visible spectroscopic results confirmed the complex formation (Cu 2+ +S1) with copper ions, but not with the other ions. Analysis of non‐covalent interactions (NCI) of ligand S1 with Ni 2+, Cu 2+ and Zn 2+ in DMSO were investigated by density functional theory (DFT). NCI analysis of S1 by Cu 2+ ions in DMSO was in good agreement with the experimental results. S2 did not react with any metal ions used in this study to form a complex in DMSO and the same was confirmed by UV‐Visible spectra. Reasonably good antibacterial activity was observed with S1, S2, Cu 2+ +S1 compared to amoxicillin against Gram‐negative bacteria ( K. pneumoniae, E. coli ), Gram‐positive bacteria ( S. aureus, S. pneumoniae ), and fungal strain ( C. albicans ). Abstract : Detection of copper ions with (E)‐N′‐((1H‐pyrrol‐2‐yl) methylene)isonicotinohydrazide (S1) was observed with naked eye visualisation and confirmed with UV‐Visible spectroscopy (experimental) and non‐covalent interactions with density functional theory (DFT) calculations (Theoretical).